New species of oak gallwaps from Iran (Hymenoptera: Cynipidae: Cynipini) - Tavakoli, M.; Melika, G.; Sadeghi, S. E.; Pénzes, Z.; Assareh, M. A.; Atkinson, R.; Bechtold, M.; Mikó, I.; Zargaran, M. R.; Aligolizade, D.; Barimani, H.; Bihari, P.; et al. (Zootaxa, 2008)
Fourteen new species of oak gallwasps, Andricus istvani, Andricus assarehi, Andricus schoenroggei, Andricus csokai, Andricus chodjaii, Andricus megatruncicolus, Andricus coriariformis, Andricus libani, Andricus stellatus, Andricuspseudoaries, Andricus sadeghii, Andricus atkinsonae, Andricus pujadevillari and Dryocosmus caspiensis (Hymenoptera: Cynipidae: Cynipini) are described from Iran. Data on the diagnosis, distribution and biology of new species are given.